PARP inhibition protects against alcoholic and non-alcoholic steatohepatitis - Mukhopadhyay, Partha; Horváth, Béla; Rajesh, Mohanraj; Varga, Zoltán V.; Gariani, Karim; Ryu, Dongryeol; Cao, Zongxian; Holovac, Eileen; Park, Ogyi; Zhou, Zhou; Xu, Ming-Jiang; Wang, Wei; et al. (Journal of hepatology, 2017)
[Display omitted] Mitochondrial dysfunction, oxidative stress, inflammation, and metabolic reprograming are crucial contributors to hepatic injury and subsequent liver fibrosis. Poly(ADP-ribose) polymerases (PARP) and their interactions with sirtuins play an important role in regulating intermediary metabolism in this process. However, there is little research into whether PARP inhibition affects alcoholic and non-alcoholic steatohepatitis (ASH/NASH). We investigated the effects of genetic deletion of PARP1 and pharmacological inhibition of PARP in models of early alcoholic steatohepatitis, as well as on Kupffer cell activation in vitro using biochemical assays, real-time PCR, and histological analyses. The effects of PARP inhibition were also evaluated in high fat or methionine and choline deficient diet-induced steatohepatitis models in mice. PARP activity was increased in livers due to excessive alcohol intake, which was associated with decreased NAD+ content and SIRT1 activity. Pharmacological inhibition of PARP restored the hepatic NAD+ content, attenuated the decrease in SIRT1 activation and beneficially affected the metabolic-, inflammatory-, and oxidative stress-related alterations due to alcohol feeding in the liver. PARP1−/− animals were protected against alcoholic steatohepatitis and pharmacological inhibition of PARP or genetic deletion of PARP1 also attenuated Kupffer cell activation in vitro. Furthermore, PARP inhibition decreased hepatic triglyceride accumulation, metabolic dysregulation, or inflammation and/or fibrosis in models of NASH. Our results suggests that PARP inhibition is a promising therapeutic strategy in steatohepatitis with high translational potential, considering the availability of PARP inhibitors for clinical treatment of cancer. Poly(ADP-ribose) polymerases (PARP) are the most abundant nuclear enzymes. The PARP inhibitor olaparib (Lynparza) is a recently FDA-approved therapy for cancer. This study shows that PARP is overactivated in livers of subjects with alcoholic liver disease and that pharmacological inhibition of this enzyme with 3 different PARP inhibitors, including olaparib, attenuates high fat or alcohol induced liver injury, abnormal metabolic alteration, fat accumulation, inflammation and/or fibrosis in preclinical models of liver disease. These results suggest that PARP inhibition is a promising therapeutic strategy in the treatment of alcoholic and non-alcoholic liver diseases.